Cytotoxic assay of RX-TRA towards Chang and HepG2 liver cell lines / Fadhilah Ismail - Ismail, Fadhilah (2015)
Cancer is one of the major health problems. More than 1 million cases of invasive cancers and half a million of cancer deaths have been reported by US Cancer Statistic in year 1999-2011. Treatment usually comprised of surgery, cytotoxic and radiation therapy which have been associated with adverse effects. More tolerable alternative treatment is highly sought by patients and one of it is natural product. Rx-Tra is one of the popular options for alternative treatment. It has been used to treat several diseases. Testimonies by patients claimed positive effects on cancer whereby patients regain their health. This study was conducted to study the cytotoxic effect of Rx-Tra towards Chang normal liver cell and HepG2 liver cancer cell lines and to study the cytotoxic effect of Rx-Train combination with Rx-17. Cell-based study had being conducted using high and low concentration of test product, where in each experiment test product was further diluted to several lower concentrations. Solvents used are double distilled water, Rx-17 and normal drinking water to see the effect of different solvents toward the effects of the test product on both cell lines. Consistent results were not obtained, thus failed to determine the IC50 of each combination of test product and solvents. Rx-17 resulted in increased cell viability for both Chang and HepG2 cell lines. From the results, it can be concluded that the best combination for Chang cell line is Rx-Tra with Rx-17, whereas the best combination to inhibit growth of HepG2 cell lines is Rx-Tra with double distilled water.